1996
DOI: 10.1002/(sici)1098-1101(1996)11:4<211::aid-jca6>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Anti-dsDNA antibody kinetics during in vivo apheresis in systemic lupus erythematosus patients and in an in vitro apheresis model

Abstract: Levels of anti‐dsDNA measured just after an immunoadsorption procedure in systemic lupus erythematosus (SLE) patients are sometimes paradoxically larger than those measured just before the procedure. A 1:100 in vitro single‐compartment immunoadsorption system model was devised to determine which of two models, one‐ or two‐compartment, more closely approximates the kinetics of anti‐dsDNA during apheresis procedures. Ten SLE patients were employed in this study. A total of 4,100 ml of plasma was passed through t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…However, in one patient, the level of anti‐DNA, as determined by RIA, paradoxically increased during the apheresis procedure (15). Accordingly, the anti‐DNA titer just after the procedure became larger than that before the treatment.…”
Section: A Compartment Model Analysismentioning
confidence: 90%
See 1 more Smart Citation
“…However, in one patient, the level of anti‐DNA, as determined by RIA, paradoxically increased during the apheresis procedure (15). Accordingly, the anti‐DNA titer just after the procedure became larger than that before the treatment.…”
Section: A Compartment Model Analysismentioning
confidence: 90%
“…A 1:100 in vitro scale, single-compartment immunoadsorption system model was devised to analyze the antibody kinetics during treatment (15). In 8 of 10 patients, the log of RIA-measured anti-DNA titers decreased in a linear manner in accordance with the increased treated plasma volume, in both the clinical procedures and the experimental model.…”
Section: A Compartment Model Analysismentioning
confidence: 99%
“…Recently, a new device has been developed which can effectively remove effectively autoantibodies and unknown materials from the blood of patients with SLE 41−45 . Although the effectiveness of this treatment itself was limited and did not last long, this therapy is now known to be useful following the combination with immunosuppressive drugs in patients with severe SLE.…”
Section: Discussionmentioning
confidence: 99%
“…Apheresis with dextran sulfate is widely used for low‐density lipopolysaccharide‐cholesterol removal (3) and was previously used for apheresis in SLE in Japan (1,4–8). Suzuki et al (9) have shown that cationic anti‐ds‐DNA antibodies bind to dextran sulfate in in vivo and in vitro models. No such antibodies could be detected in the presented case at the beginning of apheresis.…”
Section: Discussionmentioning
confidence: 99%